THEY ARE IN THE QURAN - Poppy Hippy; Mardan; Muhammad Yusuf (PT. Jurnal Center Indonesia Publisher, 2025)
Human rights are rights that are owned by all people according to humane conditions. These human rights are always seen as something basic, fundamental and important. Therefore, the opinion that says that human rights are